2021
DOI: 10.3389/fphys.2021.759035
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Exosomal Mir-423-5p Is Involved in the Occurrence and Development of Bicuspid Aortopathy via TGF-β/SMAD2 Pathway

Abstract: Objectives: Patients with bicuspid aortic valve (BAV) are at increased risk for ascending aortic dilation (AAD). Our study was aimed at systemically analyzing the expression profile and mechanism of circulating plasma exosomal microRNAs (miRNAs) related to BAV and AAD.Methods: We isolated plasma exosomes from BAV patients (n=19), BAV patients with AAD (BAVAD, n=26), and healthy tricuspid aortic valve individuals with low cardiovascular risk (TAVnon, n=16). We applied a small RNA sequencing approach to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…MiR-423-5p has been shown to interact with multiple target genes. For example, Zhang et al (2021) 73 showed that miR-423-5p levels were upregulated in exosomes from the plasma of bicuspid aorta valve (BAV) patients and could regulate TGF-β signaling by decreasing SMAD2 expression. Furthermore, miR-423-5p has been shown to regulate cell apoptosis by enhancing caspase 3/7 activity and impairing mitochondrial functionality by directly targeting Myb-related protein B (MYBL2) expression in a model of hypoxia/reoxygenation 74 .…”
Section: Discussionmentioning
confidence: 99%
“…MiR-423-5p has been shown to interact with multiple target genes. For example, Zhang et al (2021) 73 showed that miR-423-5p levels were upregulated in exosomes from the plasma of bicuspid aorta valve (BAV) patients and could regulate TGF-β signaling by decreasing SMAD2 expression. Furthermore, miR-423-5p has been shown to regulate cell apoptosis by enhancing caspase 3/7 activity and impairing mitochondrial functionality by directly targeting Myb-related protein B (MYBL2) expression in a model of hypoxia/reoxygenation 74 .…”
Section: Discussionmentioning
confidence: 99%
“…This could confound the phenotypic effect of the modulation of a specific miRNA. For example, Zhang et al (2021) [ 73 ] showed that miR-423-5p levels were upregulated in exosomes from the plasma of bicuspid aorta valve (BAV) patients and could regulate TGF-β signaling by decreasing SMAD2 expression. Furthermore, miR-423-5p was shown to regulate cell apoptosis by enhancing caspase 3/7 activity and impairing mitochondrial functionality by directly targeting Myb-related protein B (MYBL2) expression in a model of hypoxia/reoxygenation [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies described the differential expression of miRNAs between BAV and TAV (tricuspid aortic valve) patients [ 91 ]. Some studies reported that BAV aortopathy is also characterized by a lower expression of End-Mt markers compared with sporadic TAAs [ 8 , 92 ]. However, some studies demonstrated that, before dilation, BAV aortas showed an activation of the End-Mt process [ 93 ].…”
Section: Mirna Regulation Of Vascular Cell Phenotype In Genetic Taasmentioning
confidence: 99%